2020
DOI: 10.1093/nar/gkaa652
|View full text |Cite
|
Sign up to set email alerts
|

LOTUS domain is a novel class of G-rich and G-quadruplex RNA binding domain

Abstract: LOTUS domains are helix-turn-helix protein folds identified in essential germline proteins and are conserved in prokaryotes and eukaryotes. Despite originally predicted as an RNA binding domain, its molecular binding activity towards RNA and protein is controversial. In particular, the most conserved binding property for the LOTUS domain family remains unknown. Here, we uncovered an unexpected specific interaction of LOTUS domains with G-rich RNA sequences. Intriguingly, LOTUS domains exhibit high affinity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Two LOTUS variants have been distinguished: the minimal LOTUS (mLOTUS) and the extended LOTUS (eLOTUS), whose defining feature is an additional C-terminal alpha-helix in a region that appears disordered in minimal LOTUS domains ( Jeske et al, 2017 ). A recent study has identified binding of RNA G-quadruplex secondary structures as an ancient conserved function of mLOTUS domains across kingdoms, and suggests that protein binding by eLOTUS domains may be a more recent evolutionary innovation ( Ding et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two LOTUS variants have been distinguished: the minimal LOTUS (mLOTUS) and the extended LOTUS (eLOTUS), whose defining feature is an additional C-terminal alpha-helix in a region that appears disordered in minimal LOTUS domains ( Jeske et al, 2017 ). A recent study has identified binding of RNA G-quadruplex secondary structures as an ancient conserved function of mLOTUS domains across kingdoms, and suggests that protein binding by eLOTUS domains may be a more recent evolutionary innovation ( Ding et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…MIP-1 and MIP-2 can self-associate and form heterodimers through their LOTUS domains, and MIP-2 also interacts with MIP-1 through its largely disordered C-terminal region. Although we do not know if MIPs bind RNAs directly, this is a distinct possibility given the tendency of many IDRs to bind RNA and the evolutionary conservation of G-quadruplex binding among LOTUS domains ( Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Right) Predicted three-dimensional structures of LOTUS1 (top) and LOTUS2 (bottom) domains in MIP-1 and MIP-2 (also see Figure S1). study has identified binding of RNA G-quadruplex secondary structures as an ancient conserved function of mLOTUS domains across kingdoms, and suggests that protein binding by eLOTUS domains may be a more recent evolutionary innovation (Ding et al, 2020).…”
Section: Novel Lotus-domain Proteins Interact With Meg-3 In Vivomentioning
confidence: 99%
“…[23] The function of these G-rich and G4 interactions remains unclear but could be instrumental to the role of LOTUS in RNA metabolism and regulation. [23] TDRD5 and TDRD7 contain LOTUS domains paired with Tudor scaffolding domains. [24] Tudor domains have been shown to bind methylated arginines and lysines, with some preference for Argonaute proteins and histone tails.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] In addition to interfacing with proteins, LOTUS domains also bind RNA with a preference for G-rich RNAs and those that form a G-quadruplex (G4) secondary structure. [23] The function of these G-rich and G4 interactions remains unclear but could be instrumental to the role of LOTUS in RNA metabolism and regulation. [23] TDRD5 and TDRD7 contain LOTUS domains paired with Tudor scaffolding domains.…”
Section: Introductionmentioning
confidence: 99%